(untitled) (Open Academia: Journal of Scholarly Research, 2025)
This article examines the socio-economic significance of developing the service sector as a key driver of modern economic growth and social stability. It outlines the historical evolution of services, particularly the impact of the industrial revolution in shifting economies from production-centered to service-oriented models. The paper explores essential factors to consider in the transformation of service industries, including innovation, localization, and improved service delivery standards. Special attention is paid to Uzbekistan’s national programs and strategic initiatives aimed at expanding and modernizing its service sector. Furthermore, the article analyzes how service development fosters employment opportunities, enhances living standards, and supports sustainable economic progress.